OPTIMALISASI SCREW PRESS KOPRA UNTUK MENINGKATKAN PENDAPATAN MASYARAKAT MELALUI PENCIPTAAN NILAI TAMBAH KOMODITAS KELAPA - Riyadi, Slamet; Herdiana, Ade (Universitas Majalengka, 2019)
Coconut trees are widely spread in Indonesia, generally in rural areas. People usually sell coconuts to middlemen and some are processed by themselves for copra. Processing coconut into dried coconut (copra) can be done through the process of drying by the sun or using a machine. Copra processing to produce coconut oil in the region is usually done traditionally by tasting coconut milk over a fire, which later the water will evaporate and the remaining oil and pulp. Because the method is still very traditional, the process needed to produce coconut oil takes about five to six hours. Therefore, it is necessary to apply the technology of the screw palm press tool is a technology that has been designed to accelerate the production process so as to save labor, fuel and practical use. The results of research and design of copra screw press machines that have been completed in the form of design drawings using solid work applications. Machine dimension refers to a simple machine with copra storage tube material using a steel pipe with a thickness of 5 millimeters. For skeletal materials using U profile steel, L profile steel. Electric motor power and transmission systems use 0.5 HP gearbox, chain, gear measuring 36 and 14 v-belts and pulleys measuring 15 and 10. In the manufacturing process adapted to the design data and using production machines that have been adapted to the needs in the process of making tools. With the manufacturing solution, the screw press palm tool is veryhelp forcopra prcessors top produce coconut oil. For copra weighing 3 kg can produce 1 kg of oil, copra weighing 6 kg produce 2 kg of oil and copra 10 kg can produce 4 kg of oil.